Internal consultant : drawing on inside expertise - Meislin, Marcia (Crisp Pub. Menlo ParkUS, 1997)
Explains the role of an internal consultant and defines his task. Presents the skills needed by an internal consultant using the acronym, CONSULTS. Looks at understanding and working with resistance; and suggests strategies for marketing oneself as an internal consultant.